First environmental survey of Scedosporium species in Lebanon - Mina, Sara; Yaakoub, Hajar; Razafimandimby, Bienvenue; Dwars, Elske; Wéry, Méline; Papon, Nicolas; Meyer, Wieland; Bouchara, Jean-Philippe (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundScedosporium species are filamentous fungi causing a wide spectrum of infections in healthy and debilitated individuals. Despite their clinical significance, the ecology of Scedosporium species remains understudied, particularly in the Middle East.MethodsIn this context, we conducted an environmental study to elucidate the distribution and ecological preferences of Scedosporium species in the North of Lebanon. One hundred and fifty-five soil samples were collected from different environmental areas and analyzed for several chemical parameters. Scedosporium isolates were then selected for species identification and genotyping.ResultsOverall, 39 (25.16%) were positive for Scedosporium species, with a predominance of S. apiospermum (80.56%). Soil analysis revealed associations between the fungal presence and pH, nitrogen, phosphorus, and organic matter content. Moreover, genotyping analysis using MultiLocus Sequence Typing identified five major clusters. Interestingly, a number of Lebanese isolates formed an Asian-specific cluster (V) with one clinical Chinese isolate, whereas two clusters (II and III) showed a close association with German isolates, and clusters (I and IV) contained isolates with a global distribution.ConclusionThese findings provide new insights into the ecology of Scedosporium species, bridging a gap in our knowledge of their distribution on the Asian continent and laying the groundwork for future clinical investigations. Future international collaborations are essential to trace the origin of S. apiospermum.